Turbine Engine Reliability Analysis Using Reliability Availability Maintainability (RAM) - Novareza, Oyong; Darmawan, Zefry; Setyanto, Nasir Widha; Mohamad, Effendi Bin (Universitas Negeri Malang, 2024)
Electrical energy is a vital necessity characterized by ever-increasing electricity consumption. The most dominating power plant in Indonesia in supplying electricity is the steam power plant, which is 50%. In its implementation, there is damage that occurs where the highest damage is to the general unit with the highest damage to the turbine unit. Therefore, the author uses the reliability, availability, and maintainability method or RAM. The purpose of this study is to determine the value of RAM on the turbine system at PLN and provide recommendations for improvements to system performance. The results showed that the MTTF and MTTR values of the components are 112,916 minutes and 7,705.91 minutes, respectively. The MTTF value of the equipment indicates in one year the shutdown occurs 4 to 5 times with a relatively short period of time to repair. RAM analysis is carried out and the value is 4.96% (reliability), 93.612% (availability), and 36.44% (maintainability). It can be interpreted that reliability of the system is low due to the frequency of errors, quite difficult to do a repair procedure, but the system is fairly working in good condition in a year period.